Status of the linear accelerator-injector at the TNK facility - Anchugov, O.V.; Chernov, K.N.; Filiptchenko, A.V.; Gudkov, B.A.; Kokin, E.N.; Matyash, N.V.; Medvedko, A.S.; Ostreiko, G.N.; Ruvinsky, S.I.; Serdobintsev, G.V.; Ushakov, V.A. (Вопросы атомной науки и техники, 2008)
In 2006, the work was continued at the linear accelerator-injector of TNK facility, Zelenograd. In November-December, the linear accelerator conditioning was carried out to increase the output electron energy. The accelerated electron beam was obtained at the Faraday's cup located in the plane which was equivalent to the booster ring entrance point. The paper presents the accelerating structure conditioning results and diagrams of the beam pulse shape at the accelerator output and energy spectrum at the booster ring input. В 2006 р. були продовжені роботи на лінійному прискорювачі-інжекторі комплексу ТНК м. Зеленоград. У листопаді-грудні було проведене тренування лінійного прискорювача з метою підвищення енергії електронного пучку на виході ЛП, а також був отриманий прискорений електронний пучок на циліндрі Фарадея, що перебуває в площині, еквівалентній входу пучка в малий накопичувач. Представлено результати тренування прискорювальної структури, а також графіки форми імпульсу струму пучка на виході ЛП і енергетичного спектру пучка на вході в малий накопичувач. В 2006 г. были продолжены работы на линейном ускорителе-инжекторе комплекса ТНК г. Зеленоград. В ноябре-декабре была проведена тренировка линейного ускорителя с целью повышения энергии электронного пучка на выходе ЛУ, а также получен ускоренный электронный пучок на цилиндре Фарадея, который находится в плоскости, эквивалентной входу пучка в малый накопитель. Представлены результаты тренировки ускоряющей структуры, а также графики формы импульса тока пучка на выходе ЛУ и энергетического спектра пучка на входе в малый накопитель.